2005
DOI: 10.1111/j.1468-1331.2004.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs alter reproductive endocrine hormones in men with epilepsy

Abstract: Disturbances of reproductive endocrine hormones are more often found in men with epilepsy than in the general population. There is an ongoing debate whether this can be attributed to chronic use of antiepileptic drugs or to the epilepsy itself. The aim of the present study was to evaluate the degree of endocrine disturbances in men with epilepsy compared with healthy controls, and to investigate whether there was a drug-specific effect of valproate (VPA) or carbamazepine (CBZ). Men with epilepsy, 20-40 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 47 publications
7
37
0
6
Order By: Relevance
“…Then rats were kept in glass cages in pairs and they were filmed by cameras for 1 hour in darkness. This information (erection, ejaculation and cup) was recorded (23).…”
Section: Weighing the Tissue Of The Testesmentioning
confidence: 99%
“…Then rats were kept in glass cages in pairs and they were filmed by cameras for 1 hour in darkness. This information (erection, ejaculation and cup) was recorded (23).…”
Section: Weighing the Tissue Of The Testesmentioning
confidence: 99%
“…Concerning the effects of valproate (VPA) on the levels of steroids and related substances, except Røste et al [42], who found higher LH levels in VPA treated male patients than in the control group, most authors did not find an effect of VPA on the LH levels [38,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Although, some studies reported no effect of VPA on FSH levels [38,43], most studies found lower FSH levels in VPA treated patients than in controls [42,46] or even suppression of FSH by VPA therapy [44,45]. In addition, no effect of VPA on the LH/FSH ratio was reported by Stephen et al [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore chronic treatment with VPA has been associated with a variety of endocrine related side effects, suggesting that VPA acts at multiple levels within CNS. VPA administration decreases secretion of anterior pituitary hormones such as luteinizing hormone (LH) and follicle stimulating hormone (FSH) (Roste et al 2005). Increase in mean serum levels of serum hormone binding globulin (SHBG) ) is another reported side effect of VPA medication.…”
Section: Introductionmentioning
confidence: 99%